Microcrystal Electron Diffraction (MicroED) for Small‐Molecule Structure Determination. Issue 3 (12th December 2018) - Kunde, Tom; Schmidt, Bernd M.
Abstract: The development of new methods to analyze and determine molecular structures parallels the ability to accelerate synthetic research. For many decades, single‐crystal analysis by X‐ray diffraction (SXRD) has been the definitive tool for structural analysis at the atomic level; the drawback, however, is that a suitable single crystal of the analyte needs to be grown. The recent innovation of the crystalline sponge (CS) method allows the microanalysis of compounds simply soaked in a readily prepared CS crystal, thus circumventing the need to screen crystallization conditions while also using only a trace amount of the sample. In this context, electron diffraction for the structure determination of small molecules is discussed as potentially the next big development in this field. Abstract : e ‐‐ ‐lucidation of structures : The microcrystal electron diffraction (MicroED) method promises to significantly accelerate the ability of synthetic chemists to gain structural information about small organic molecules and might be crucial for the acceleration of innovations across many fields.